The Relationship of Handwriting, Spelling and Word Reading Accuracy Among Multilingual Primary 1 Poor Readers - Joanna Joo Ying, Wang (Academy Publication, 2024)
This study aimed to investigate the relationship of handwriting, spelling and word reading accuracy among multilingual Primary 1 poor readers. A total of 866 Year 1 Malaysian government school students from various demographic and multilingual backgrounds participated in the research. Students with poor reading skills were classified according to percentile scores with the 25th percentile and below as the cut-off point. The reading (word reading accuracy), spelling (phonological coding) and handwriting (name and letter writing) outcomes were analysed. The findings show that a majority of poor readers, respectively in Malay and English, had poor handwriting and spelling skills. Spelling was a better indicator for identifying reading difficulties due to its high correlations with reading performance. Additionally, both poor readers and spellers correspondingly showed poor reading and spelling performances in both languages. These findings are useful for developing more appropriate tools to identify reading difficulties among Malaysian learners. Future directions and implications for practice are addressed.